Persepsi Konsumen Terhadap Promosi Wajit Cililin Wajit Pusaka Utama Ibu Hj. Erum di Instagram - Bandana Nararya Aryadi; Patria Supriyoso (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
The advancement of digital technology encourages micro, small, and medium enterprises (MSMEs) to adopt social media as a promotional tool, including for traditional food products. Wajit Cililin, a traditional snack from West Bandung Regency, faces the challenge of maintaining its existence amid changing consumer behavior. This study aims to analyze the promotional strategies of Wajit Pusaka Utama Ibu Hj. Erum through Instagram and to identify consumer perceptions of these promotional efforts.This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews with the business owner and consumers, observations of the Instagram account, and documentation of promotional content. Data analysis techniques used Miles and Huberman’s model, which includes data reduction, data display, and conclusion drawing.The findings reveal that Wajit Pusaka Utama utilizes Instagram by combining engaging visual content and cultural narratives to build a traditional product image. Consumer perceptions of the promotion are generally positive, as the content successfully introduces cultural values while generating consumer interest. Digital promotion through Instagram has proven effective in expanding market reach and preserving local cultural values.